2018
DOI: 10.3389/fvets.2018.00259
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of BCG Vaccine for Control of Tuberculosis in Domestic Livestock and Wildlife

Abstract: Bovine tuberculosis (TB) continues to be an intractable problem in many countries, particularly where “test and slaughter” policies cannot be implemented or where wildlife reservoirs of Mycobacterium bovis infection serve as a recurrent source of infection for domestic livestock. Alternative control measures are urgently required and vaccination is a promising option. Although the M. bovis bacille Calmette-Guérin (BCG) vaccine has been used in humans for nearly a century, its use in animals has been limited, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 128 publications
(138 reference statements)
1
114
1
Order By: Relevance
“…In wildlife one requirement for a vaccine is that it should be administered using baits by oral route. At the moment only BCG is allowed for intramuscular administration to badgers in the UK since 2010, but there are limitations for delivery in the field (16). Based on our data, HIMB vaccination appears to be a promising oral vaccine candidate for badgers, pending further development for large scale production, incorporation in baits, minimum protective doses, duration of immunity, safety, and assessment in field conditions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In wildlife one requirement for a vaccine is that it should be administered using baits by oral route. At the moment only BCG is allowed for intramuscular administration to badgers in the UK since 2010, but there are limitations for delivery in the field (16). Based on our data, HIMB vaccination appears to be a promising oral vaccine candidate for badgers, pending further development for large scale production, incorporation in baits, minimum protective doses, duration of immunity, safety, and assessment in field conditions.…”
Section: Discussionmentioning
confidence: 92%
“…Vaccination of badgers has been proposed as a long-term control strategy for the disease in the UK and Ireland (6)(7)(8) and experimental studies have demonstrated that vaccination with live attenuated bacillus Calmette-Guérin (BCG) vaccine is protective in badgers, and also in wild boar (9)(10)(11)(12)(13)(14)(15). However, the use of a live vaccine (BCG) at protective doses in badger is only licensed in the UK by the intramuscular route and its use in baits is controversial (16). That is because there are particular challenges associated with the development of a live oral BCG vaccine, not least maintaining the survival of BCG in baits until deployment in the field, but also with issues arising from release of a live vaccine into the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Although BCG vaccination does not induce complete protection, no single vaccine has proven to be more efficacious than BCG to protect cattle against bTB. Recent studies have shown that similar levels of protection were induced when BCG was applied parenterally or orally, although higher doses were required for oral vaccination (Buddle et al., ). The highest level of efficacy was achieved when calves were vaccinated at <1 month of age, followed by a revaccination boost at 12–24 months to prevent waning immunity (Parlane et al., ).…”
Section: Bcg Vaccination Of Cattlementioning
confidence: 99%
“…Therefore, induction of mucosal immunity could be beneficial and oral vaccination with BCG might be advantageous. Preliminary research into the use of oral BCG to protect cattle against bTB has been encouraging,(Buddle, Vordermeier, Chambers, & de Klerk‐Lorist, ; Nugent, Yockney, Whitford, Aldwell, & Buddle, ) as has been its application in wildlife reservoirs, such as possums in New Zealand (Tompkins et al., ) and badgers in Ireland (Gormley, Ní Bhuachalla, O'Keeffe, Murphy, & Aldwell, ). This experience, as well as the effective administration of rabies vaccine using bait, suggests that oral administration of BCG vaccine might be the most cost‐effective means of vaccinating wildlife (Pastoret & Brochier, ).…”
Section: Efficacy Of Oral Bcgmentioning
confidence: 99%
See 1 more Smart Citation